LANGUAGE STYLE USED IN OPRAH WINFREY’S TALK SHOW ON YOUTUBE - Febrianti, Nova; Efendi, Dedi; Oktariza, Dodi (Universitas Muara Bungo, 2023)
This research analyzes the types of language styles used in Oprah Winfrey’s talk show, starring The Rock (Dwayne Johnson) in 2020 and how each language style serves their own specific language function. The purposes of this research are (1) to find out the language styles used on Oprah Winfrey's talk show; (2) to find out the functions of the speaker’s dialogues in using language style. The analysis is conducted based on the theory by Joos (1967) on language styles and Jakobson (2011) on functions of language styles. The research applied descriptive qualitative method and the data were obtained from the Oprah Winfrey’s talk show on YouTube. Tables are also used to present the data analysis in this research.The findings of this research shows that: First, out of 21 data obtained from the talk show, there are only 3 language styles used in Oprah Winfrey’s talk show, which are formal style (2 data), consultative style (5 data), and casual style (14 data) which was applied the most throughout the talk show; Second, the 21 data of language styles used in the talk show represent their own specific functions, which are referential function (3 data), directive function (2 data), expressive function (8 data), social function (5 data), and poetic function (3 data), with expressive function as the most common function in the talk show